Pengaruh Aksesbilitas Modal Usaha, Loyalitas Karyawan, Penggunaan Aplikasi Pesan Antar Terhadap Penjualan Usaha Mikro Kecil Menengah (UMKM) Bidang Food And Beverage Di Kecamatan Kebon Jeruk, Jakarta Barat Tahun 2022 - Syifa Wulandari; Sri Indah Nikensari; Karuniana Dianta (Peneliti.net, 2023)
This study aims to analyze the accessibility of business capital, employee loyalty, and the intensity of using the delivery application on sales of micro, small and medium enterprises (MSMEs) in the food and beverage sector in West Jakarta in 2022. The independent variable in this study is MSME sales. Then the dependent variable in this study is the accessibility of business capital, employee loyalty, and the intensity of using the delivery application. In this study the method used was quantitative descriptive analysis, using multiple regression analysis with the SPSS program. The data used in this research is primary data from structured interviews via Google forms with 44 respondents. The results of this study suggest that there is an influence of business capital accessibility on sales of micro, small and medium enterprises in Kebon Jeruk District. there is the Effect of Employee Loyalty on Sales of Micro, Small and Medium Enterprises in Kebon Jeruk District. there is an Influence of Intensity Use of Delivery Applications on Sales of Micro, Small and Medium Enterprises in Kebon Jeruk District